we are given the following expression and we are to factorize it:
we are to find factors of 36 such that when multiplied they give a product of 36 and when added they give a result of -13.
therefore, the factored form of the given expression is (d-4)(d-9).
we took $ 24 to the movies.
let total money be
on movies = half of the money =
on popcorn =
on candy = $2
on soda = $3
total money spent = ++ 2+3+1
x = ++ 2+3+1
x- - = 6
- - =6
given that in a sequence general term i.e. nth term is given by
to find out the first term and pattern of term and compare with those given
to find first term put n=1
let us find
hence both the statements are the same.
or both sequences meant by two different conditions are one and the same